DNA-PKcs chemical inhibition versus genetic mutation: Impact on the junctional repair steps of V(D)J recombination. (April 2020) - Anne Esguerra, Z.; Watanabe, Go; Okitsu, Cindy Y.; Hsieh, Chih-Lin; Lieber, Michael R.
Highlights: Engineered KO of DNA-PKcs expression impacts V(D)J coding joint formation much more than signal joint formation. Here, chemical inhibition of DNA-PKcs reduces Artemis endonuclease activity in a purified system. Cellular V(D)J effects of a DNA-PKcs chemical inhibitor show a reduction in coding joint formation relative to signal joint formation. The recombination signal DNA end resection observed in DNA-PKcs genetic mutants is not seen with chemical inhibition. Abstract: Spontaneous DNA-PKcs deficiencies in animals result in a severe combined immunodeficiency (SCID) phenotype because DNA-PKcs is required to activate Artemis for V(D)J recombination coding end hairpin opening. The impact on signal joint formation in these spontaneous mutant mammals is variable. Genetically engineered DNA-PKcs null mice and cells from them show a >1, 000-fold reduction in coding joint formation and minimal reduction in signal joint formation during V(D)J recombination. Does chemical inhibition of DNA-PKcs mimic this phenotype? M3814 (also known as Nedisertib) is a potent DNA-PKcs inhibitor. We find here that M3814 causes a quantitative reduction in coding joint formation relative to signal joint formation. The sequences of signal and coding junctions were within normal limits, though rare coding joints showed novel features. The signal junctions generally did not show evidence of resection into the signal ends that is often seen in cells that have genetic defects in DNA-PKcs. Comparison of the chemical inhibition findings here with the known results for spontaneous and engineered DNA-PKcs mutant mammals is informative for considering pharmacologic small molecule inhibition of DNA-PKcs in various types of neoplasia.